Belgium : Recent Economic Developments. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1996)
This paper describes economic developments in Belgium during the 1990s. The moderate recovery experienced by Belgium in 1994 slowed in the course of 1995 as foreign demand faltered, and GDP growth for 1995 as a whole is now estimated at 2 percent. Domestic demand was supported by increased investment, but private consumption growth remained anemic as real disposable household income grew little. Since early 1994, the Belgian franc has generally been slightly appreciated relative to its central parity against the deutsche mark.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet